Pengelompokan Kabupaten/Kota di Indonesia Berdasarkan Indikator Teknologi Informasi dan Komunikasi Menggunakan Metode K-Means - Yudistira, Muhammad Rizki; Maulana, Rifki (Seminar Nasional Official Statistics, 2025)
The development of Information and Communication Technology (ICT) in Indonesia continues to show positive trends, yet regional disparities remain a significant challenge. This study aims to cluster regencies and municipalities in Indonesia based on ICT development indicators using the non-hierarchical K-Means clustering method. The data were derived from the 2024 SUSENAS survey, using four key variables: mobile phone ownership, computer literacy, internet usage, and average years of schooling. The analysis identified three major clusters with varying ICT development characteristics. The highest-performing cluster is dominated by urban areas, while the lowest-performing cluster is concentrated in eastern Indonesia. These findings highlight a significant digital divide, indicating the need for affirmative policies to promote equitable access, usage, and digital skills development across the country.